2014
DOI: 10.3762/bjoc.10.296
|View full text |Cite
|
Sign up to set email alerts
|

Binding mode and free energy prediction of fisetin/β-cyclodextrin inclusion complexes

Abstract: SummaryIn the present study, our aim is to investigate the preferential binding mode and encapsulation of the flavonoid fisetin in the nano-pore of β-cyclodextrin (β-CD) at the molecular level using various theoretical approaches: molecular docking, molecular dynamics (MD) simulations and binding free energy calculations. The molecular docking suggested four possible fisetin orientations in the cavity through its chromone or phenyl ring with two different geometries of fisetin due to the rotatable bond between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 49 publications
2
38
1
Order By: Relevance
“…On the other hand, the main contribution for eucalyptol inclusion arises from the van der Waals interaction (DE vdW of at least À20 kcal mol À1 ). Similar to our previous studies, 35,37,38,55 the van der Waals forces were found to play a key role in the formation of inclusion complexes between CDs and the non-polar guest molecules. The solvation free energies (DG solv ) predicted by the PBSA and GBSA approaches suggest that the different solvation effects in the modied bCDs slightly increased with PBSA or decreased with GBSA relative to bCD.…”
Section: Binding Free Energy Analysissupporting
confidence: 89%
See 2 more Smart Citations
“…On the other hand, the main contribution for eucalyptol inclusion arises from the van der Waals interaction (DE vdW of at least À20 kcal mol À1 ). Similar to our previous studies, 35,37,38,55 the van der Waals forces were found to play a key role in the formation of inclusion complexes between CDs and the non-polar guest molecules. The solvation free energies (DG solv ) predicted by the PBSA and GBSA approaches suggest that the different solvation effects in the modied bCDs slightly increased with PBSA or decreased with GBSA relative to bCD.…”
Section: Binding Free Energy Analysissupporting
confidence: 89%
“…The total host-guest binding free energy (DG bind ) was estimated by means of MM-PBSA/GBSA approaches in accordance with the other avonoid/CD inclusion complexes. 35,37 Furthermore, the DG bind was subsequently corrected by replacing the MM energy (DE MM ) with energy obtained the from quantum mechanics (DE QM ) calculated at the density functional theory (DFT) with the M06-2X/6-31G(d,p) level of theory 35 using Gaussian 09. All structural analyses were computed by the cpptraj module, 70 while the DG bind was calculated using the MMPBSA.py module 71 implemented in AMBER14.…”
Section: Classical Molecular Dynamics Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the complex, protein, and ligand structures are extracted from the same trajectory, the binding free energy ( G bind ) was calculated approximately by the energy difference of the complex ( G complex ), receptor ( G receptor ), and ligand ( G ligand ) 38 . In contrast, the binding free energy (Gibbs free energy, G bind ) was calculated by adding the gas phase energy ( G gas ) and solvation free energy ( G sol ), or it was divided into two portions: enthalpy terms ( H ), which consist of molecular mechanics energy in a vacuum ( E MM ) and the solvation free energy ( G sol ), and entropy terms with constant temperature ( T Δ S ) 39 .…”
Section: Methodsmentioning
confidence: 99%
“…The top three docked complexes ranked from CDOCKER interaction energies and iGEMDOCK fitness scores were used for a 100 ns MD simulation with periodic boundary condition using the AMBER 16 program [74]. The partial charges of each ligand were prepared in accordance with the standard protocol [75][76][77], while the other parameters were taken from the general AMBER force field [74]. The AMBER ff14SB force field [78] was applied on the E protein.…”
Section: Simulations and Binding Energy Calculationsmentioning
confidence: 99%